FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN (STUDI PADA PERBANKAN SYARIAH DI INDONESIA) - Khairiah Khairiah; Raida Fuadi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this research is to determine the influence of firm size, liquidity, leverage, profitability on voluntary disclosure at syariah banking in Indonesia during 2010-2014. The type of this research is hypothesis testing by using census method in analyzing the research population. Population in this research is all of syariah banking that publish the financial report for the year 2010-2014 that consist of 11 banks. The type of data that used is secondary data, that consist of 55 financial report for five years. The testing of hypothesis used is linear regression analysis. The results of this research show that firm size, liquidity, leverage, profitability simultaneously have an effect on the voluntary disclosure. Liquidity and profitability partially have an effect on the voluntary disclosure, while firm size, and leverage have not effect on the voluntary disclosure. Keywords: voluntary disclosure, firm size, liquidity, leverage, profitability.